1977
DOI: 10.2307/2374006
|View full text |Cite
|
Sign up to set email alerts
|

The Kakeya Maximal Function and the Spherical Summation Multipliers

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . The Johns Hopkins University Press is collaborating with JSTOR to digitize, preserve and extend access to American Journal of Mathematics. I. Introduction. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(211 citation statements)
references
References 9 publications
(1 reference statement)
4
206
0
1
Order By: Relevance
“…By Theorem 3.1 the two estimates are equivalent in the triangular region below the dashed line. The point 1 is the trivial L 1 → L ∞ estimate, while the point 2 represents the higher-dimensional analogue of Cordoba's argument ( [8], [2]), and 3 is the "bush" argument as given by Bourgain [2] (see also [9], [8]). Proposition 3.2, the bilinear improvement to Cordoba's argument, is the point 4.…”
Section: Bilinear Kakeya Estimatesmentioning
confidence: 99%
“…By Theorem 3.1 the two estimates are equivalent in the triangular region below the dashed line. The point 1 is the trivial L 1 → L ∞ estimate, while the point 2 represents the higher-dimensional analogue of Cordoba's argument ( [8], [2]), and 3 is the "bush" argument as given by Bourgain [2] (see also [9], [8]). Proposition 3.2, the bilinear improvement to Cordoba's argument, is the point 4.…”
Section: Bilinear Kakeya Estimatesmentioning
confidence: 99%
“…In the present context, (2.11) is a simple consequence of a variable coefficient version of a maximal theorem of Córdoba [3] (see also [17]) involving averages of functions of two variables. We postpone the straightforward argument until the end of this section.…”
Section: Corollary 22mentioning
confidence: 91%
“…Here |Ω ∩ γ α x | denotes one-dimensional Lebesgue measure. Results of Córdoba [3] imply that such a set must have full Hausdorff dimension. For analogous sets in R 3 it is conjectured that the same should be true.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) The family of rectangles in lacunary directions in U 2 . To see that the maximal operator here is strong type 2, order the rectangles by longest sidelength; Cordoba and Fefferman [4] observed that if R a £R, then |/?…”
Section: Covering Lemmasmentioning
confidence: 99%